1993
DOI: 10.1111/j.1365-2419.1993.tb00009.x
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of cod (Gadus morhua) in relation to temperature and oxygen level in the Gulf of St. Lawrence

Abstract: Bottom temperature and oxygen level were measured in the northern Gulf of St. Lawrence during a ground‐fish trawl survey held in August and September 1991. Cumulative relative frequencies of temperature and oxygen level and cumulative relative frequencies of temperature x cod and oxygen X cod were computed with consideration of the random stratified sampling scheme. A total of 84‐3% of temperature x cod frequency cumulated from 2oC to 4oC, but only 25% of the frequency of temperature alone cumulated from 2oC t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 12 publications
(8 reference statements)
0
42
0
Order By: Relevance
“…Further, this species has traditionally inhabited areas, such as the Baltic Sea (Gerlach, 1988) and the Gulf of St Lawrence (GSL) (D'Amours, 1993;Kiceniuk and Colbourne, 1997;Gilbert et al, 2005), where they are now likely to encounter environmental oxygen levels that may strongly affect their distribution, growth and reproduction, at least during part of their life history. For example, GSL cod are sensitive to hypoxia (D'Amours, 1993), completely avoid regions of water oxygen partial pressures (Pw O2 ) below a threshold of ~6.6kPa (Kiceniuk and Colbourne, 1997), and there are thus areas in the GSL that are below the threshold for survival (Plante et al, 1998;Gilbert et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Further, this species has traditionally inhabited areas, such as the Baltic Sea (Gerlach, 1988) and the Gulf of St Lawrence (GSL) (D'Amours, 1993;Kiceniuk and Colbourne, 1997;Gilbert et al, 2005), where they are now likely to encounter environmental oxygen levels that may strongly affect their distribution, growth and reproduction, at least during part of their life history. For example, GSL cod are sensitive to hypoxia (D'Amours, 1993), completely avoid regions of water oxygen partial pressures (Pw O2 ) below a threshold of ~6.6kPa (Kiceniuk and Colbourne, 1997), and there are thus areas in the GSL that are below the threshold for survival (Plante et al, 1998;Gilbert et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxia is a common phenomenon in a range of sea areas such as the Baltic Sea and the Gulf of St Lawrence [68], as well as large parts of the eastern Tropical Pacific (ETP) and eastern Tropical Atlantic (ETA) at depths below about 100 m [33]. The oxygen-minimum zones in the tropical Pacific and Atlantic are among the largest areas of naturally occurring hypoxia in the world oceans and are predicted to expand with climate change [33].…”
Section: Telemetry and Behaviourmentioning
confidence: 99%
“…Recent studies have shown that a number of groundfish species exhibit strong and repeatable associations for a particular range of depths, temperatures, or salinities, or some combination thereof (Scott, 1982;Smith et al, 1991;Sinclair, 1992;D'Amours, 1993;Page et al, 1994;Perry and Smith, 1994;Swain and Kramer, 1995). There is also ample evidence that the amount of bottom water that exhibits these seemingly preferred characteristics or the amount of bottom water of this type being sampled can fluctuate over time and may therefore affect the availability or catchability of the species being surveyed by the trawl (Smith et al, 1991;Page et al, 1994;.…”
Section: Introductionmentioning
confidence: 99%